PREDATION OF Dryophylax chaquensis (SERPENTES: DIPSADIDAE) UPON Elachistocleis matogrosso AND Boana raniceps (ANURA) - Cavalheri, Diego Gomiero [UNESP]; Nehemy, Ibrahim Kamel Rodrigues; Cavalcante, Kélvin; Carrillo, Juan Fernando Cuestas; Santana, Diego José (Universidad Nacional de Colombia, 2023)
Anurans play a central role in food webs, being prey for different vertebrates, like snakes, mammals, fishes, and birds. The snakes from the tribe Tachymenini are known for their preference for preying on anurans, even different animals eventually being part of their diet. Data about Dryophylax chaquensis diet is resumed mainly by field observations and only anurans are known as its prey. Herein we report a field observation from Brazilian Pantanal of Dryophylax chaquensis regurgitating two anurans, Elachistocleis matogrosso and Boana raniceps. This is the first report of a Boana raniceps as prey of D. chaquensis, and the second record for Elachistocleis matogrosso. These present records confirm the bathracophagy preference of D. chaquensis and highlight the opportunistic habit of preying on frogs that are more abundant now.
Depredación de Dryophylax chaquensis (Serpentes: Dipsadidae) sobre Elachistocleis matogrosso y Boana raniceps (Anura)
Keywords: Frog; natural history; predation; snake